2022
DOI: 10.15406/jmen.2022.10.00345
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infection: challenges to public health

Abstract: Surgical site infections are healthcare-related infections that succeeds post-surgical procedures in patients, associated with risk factors. Patients admitted in, healthcare facilities and medical institutions are vulnarable to these hospital associated due to lack of suitable infrastructure and hygiene protocols. The objective was to present the etiology and risk factors associated with the onset of surgical site infection, pointing out a critical view of the challenges and appropriate measures for its preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In low income settings, advanced age, diabetes mellitus, obesity, alcoholism history, and long hospital stay post-surgery can contribute significantly to SSIs. [13] Studies conducted literature from Ethiopia and Rwanda indicated that advanced age, wound classification, experience and skills of a surgeon, blood transfusion, emergency surgery, duration of surgical operation, hemoglobin less than 7g/dl, systolic blood pressure <90mmhg , patient' surgical history, long hospital stay could likely contribute to SSIs. [14,15] Therefore, healthcare professionals should recognize aforementioned factors and apply the SSIs prevention guidelines adequately to minimize the occurrence of SSIs among patients with such risks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In low income settings, advanced age, diabetes mellitus, obesity, alcoholism history, and long hospital stay post-surgery can contribute significantly to SSIs. [13] Studies conducted literature from Ethiopia and Rwanda indicated that advanced age, wound classification, experience and skills of a surgeon, blood transfusion, emergency surgery, duration of surgical operation, hemoglobin less than 7g/dl, systolic blood pressure <90mmhg , patient' surgical history, long hospital stay could likely contribute to SSIs. [14,15] Therefore, healthcare professionals should recognize aforementioned factors and apply the SSIs prevention guidelines adequately to minimize the occurrence of SSIs among patients with such risks.…”
mentioning
confidence: 99%
“…Decolonization with mupirocin ointment, pre-op patient skin cleansing, pre-op patient hair removal, blood transfusions, standard antibiotic prophylaxis (SAP), standard antibiotic prophylaxis (SAP) prolongation, additional preoperative considerations, patient educationIntraoperative CareSterile technique, surgical attire, surgical hand antisepsis, surgical site skin antisepsis, antibiotic prophylaxis, air quality, traffic patterns, prevention of hypothermia, sterilization of surgical instrumentsPostoperative CarePostoperative incisional care, postoperative skeletal pin care, postoperative care uses of negative pressure wound therapy, disinfection of non-critical items postoperative patient and family education https://dx.doi.org/10.4314/rjmhs.v6i3 13. Rwanda Journal of Medicine and Health Sciences Vol.…”
mentioning
confidence: 99%